2016
DOI: 10.1186/s41240-016-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling effects of the periostracum on algal spore settlement in the mussel Mytilus edulis

Abstract: In nature, marine mussels (Mytilus edulis) suffer less fouling colonization on the newly formed sides of their shells. Using settlement assays with algal spores of Porphyra suborbiculata, we determined that spore attachment and germination on the periostracum decreased to 36.8 and 3.3 %, respectively. Additionally, the spore settlement was considerably diminished by periostracum dichloromethane extracts containing 19 % oleamide, a major antifouling compound. A scanning electron micrograph of the surface reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Other natural compounds, such as extracts from shellfish periostracum, exhibit strong AF properties and can be designed for commercial use. For example, periostracum dichloromethane extracts containing oleamide reduce algal spore settlement (Kang et al 2016), and crude periostracum extracts inhibit the attachment of barnacles, diatoms and marine bacteria (Bers et al 2006). Shellfish periostraca and biogenically derived microtopographies present a nontoxic, environmentally friendly substratum to prevent the settlement and attachment of a range of fouling organisms.…”
Section: Novel Antifouling Control Technologiesmentioning
confidence: 99%
“…Other natural compounds, such as extracts from shellfish periostracum, exhibit strong AF properties and can be designed for commercial use. For example, periostracum dichloromethane extracts containing oleamide reduce algal spore settlement (Kang et al 2016), and crude periostracum extracts inhibit the attachment of barnacles, diatoms and marine bacteria (Bers et al 2006). Shellfish periostraca and biogenically derived microtopographies present a nontoxic, environmentally friendly substratum to prevent the settlement and attachment of a range of fouling organisms.…”
Section: Novel Antifouling Control Technologiesmentioning
confidence: 99%
“…Our previous study showed that the shells of larger Lunella tended to be more worn out than those of smaller ones (Osawa & Tokeshi, 2018), leading to different microhabitat characteristics compared with intact shell surfaces (Figure 1c). In this respect, note that the molluscan periostracum is known to inhibit the attachment of sessile organisms; the intact periostracum of Mytilidae with ripple‐like microtopography with specific chemical substances such as diethyl ether and dichloromethane fractions inhibits the settlement of marine bacteria, diatom, and cyprids larvae (Bers, D'Souza, Klijnstra, Willemsen, & Wahl, 2006; Bers & Wahl, 2004; Bottjer, 1981; Kaehler, 1999; Kang et al, 2016; Scardino, De Nys, Ison, O'Connor, & Steinberg, 2003). It is therefore possible that lack of the antifouling periostracum in larger Lunella individuals might facilitate colonization by epibionts.…”
Section: Discussionmentioning
confidence: 99%
“…To ease the removal of periostracum, the seashells were immersed in a vinegar and seawater solution (1:2), taken in a 250 mL beaker, and left undisturbed for 24 hours. Periostracum was removed from the shell with the help of sterile forceps and retained for further experimental [11].…”
Section: Removal Of Periostracummentioning
confidence: 99%